Pengaruh Kinerja Keuangan Terhadap Return Saham Pada Beberapa Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia - Kurniaty Kurniaty; Aris Setia Noor (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2020)
This study aims to determine the effect of financial performance on stock returns in the manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange from 2014 to 2016 simultaneously or partially. The variables used in this study are Return On Assets (X1), Return On Equity (X2), Economic Value Added (X3) as the independent variable and Stock return as the dependent variable.Samples were taken as many as 20 manufacturing industry companies listed on the Indonesia Stock Exchange (IDX) during 2014 to 2016. The data used are financial reports from each sample company which are published on the website ww.idx.co.id. the data analysis method used in this study is a quantitative method by testing classic assumptions, and statistical analysis is multiple linear regression analysis. The sampling method used was purposive sampling.